Erozja autorytetu nauczyciela akademickiego – czy ta tendencja może ulec zmianie? - Polok, ks. Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2010)
The increasing trend concerning loosing respect towards honoured authorities can nowadays be observed in most of the areas of social life. This refers also to universities and decreasing respect towards academics. The study at Karol Adamiecki Univeristy of Economics in Katowice, focused on structure and hierarchy of values declared by its students, were expected to reveal whether this assumption is true. The study characterized reasons for and directions of change in the declared hierarchy of values among the young. It was of high importance to diagnose the core of interactions between students and academics, i.e. to answer a question whether academics employed by the University are perceived by the students as persons whose personal approach and behaviours could be followed. The results show that nowadays academic is not respected as an authority for her/his students. The way to regain respect seems to be based on reinforcement of traditional master (tutor) – student relations, as university is this particular place where this kind of interrelations should develop. The task of building this relation needs time and efforts, as well as sets a high standard for academics to present unimpeachable ethical approach as well as openness towards students and dynamic changes in the environment.